2021
DOI: 10.2340/16501977-2835
|View full text |Cite
|
Sign up to set email alerts
|

Changes in levels of cartilage oligomeric proteinase and urinary C-terminal telopeptide of type II collagen in subjects with knee osteoarthritis after dextrose prolotherapy: A randomized controlled trial

Abstract: Objective: To assess the effects of dextrose prolotherapy in patients with knee osteoarthritis on the levels of serum cartilage oligomeric proteinase and urinary C-terminal telopeptide of type II collagen, and on the Western Ontario McMaster Universities Index and numerical rating scale score for pain. Methods: A randomized controlled trial, in which participants were randomly allocated into 2 groups, receiving injections of either hyaluronic acid or dextrose prolotherapy. The hyaluronic acid group received 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…Five clinical trials were included in the quantitative analysis. [24][25][26][27][28] The flowchart of the systematized search is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five clinical trials were included in the quantitative analysis. [24][25][26][27][28] The flowchart of the systematized search is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…HDP has also been reported to generate some adverse reactions such as pain, inflammation, and a stiffness feeling 9 . It was observed that in the studies that reported adverse reactions, 25,28,29 63.2% of individuals treated with HDP presented pain and inflammation vs. 46.0% of those treated with HA. Minor adverse reactions such as self-limiting pain and inflammation seem to be more common in individuals treated with HDP; no major adverse reactions or side effects occurred in any participant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations